Classical Swine Fever Research for Improved Diagnostics, Vaccines and Disease Control - Dhar, Pronab; Saikumar, G. (Indian Farming, 2015)
With an estimated pig population of 11.13 millions, India needs about 10 million doses of CSF vaccine annually which are easy to produce once the cell culture vaccine is produced indigenously. Success in CSF controlling will minimize the losses incurred by pig farmers and boost pork production and contribute to the nutritional requirement of the country’s population.